2021
DOI: 10.3389/fonc.2021.709796
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Infection–Related Long Non-Coding RNA Signatures Predict the Prognostic Status for Gastric Cancer Patients

Abstract: BackgroundHelicobacter pylori (H. pylori) is a type I biological carcinogen, which may cause about 75% of the total incidence of gastric cancer worldwide. H. pylori infection can induce and activate the cancer-promoting signaling pathway and affect the occurrence and outcome of gastric cancer through controlling the regulatory functions of long non-coding RNAs (lncRNAs). However, we have no understanding of the prognostic worth of lncRNAs for gastric cancer patients infected with H. pylori.MethodWe screened di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Compared to other prognostic signatures, our study mainly focused on lncRNAs correlated with angiogenesis status, identified prognosis-related ARLncs, and developed a risk model of prognosis in patients with STAD. Previous studies have investigated several prognostic models based on lncRNA expression involved in the process of ferroptosis [ 25 ], N6-methyladenosine modification [ 26 ], or Helicobacter pylori infection [ 27 ], which induce and activate the protumor signaling pathway of gastric cancer. Thus, our risk signatures had dual roles as it predicted the prognosis of STAD and contributed to the selection of proper cohorts who may benefit from antiangiogenesis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other prognostic signatures, our study mainly focused on lncRNAs correlated with angiogenesis status, identified prognosis-related ARLncs, and developed a risk model of prognosis in patients with STAD. Previous studies have investigated several prognostic models based on lncRNA expression involved in the process of ferroptosis [ 25 ], N6-methyladenosine modification [ 26 ], or Helicobacter pylori infection [ 27 ], which induce and activate the protumor signaling pathway of gastric cancer. Thus, our risk signatures had dual roles as it predicted the prognosis of STAD and contributed to the selection of proper cohorts who may benefit from antiangiogenesis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence indicated that lncRNAs have an undeniable prognosis prediction function in GC cancer. Prognostic signatures based on ferroptosis-related lncRNA, immune-related lncRNA and helicobacter pylori infectionrelated lncRNA were proved to have preferable prognosis prediction functions in GC (Ma et al, 2021;Pan J. et al, 2021;Wei et al, 2021;Xin et al, 2021). Apart from this, lncRNAs could be used for subtype identification and therapy response prediction of GC Jiang et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a type of non-coding RNA defined as transcripts >200 nucleotides that lack the potential to encode proteins and are involved in the regulation of a variety of tumors 18,19 . In addition, some lncRNAs are closely associated with drug resistance in osteosarcoma cells 20 .…”
Section: Discussionmentioning
confidence: 99%